Efeitos da ovariectomia e do treinamento resistido sobre a função e metabolismo energético mitocondrial dos cardiomiócitos do ventrículo esquerdo - Pinto, Regiane (Universidade Federal de São Carlos, 2025)
Menopause is characterized as a physiological process marked by the cessation of menstruation, typically occurring between the fourth and fifth decades of a woman’s life. The main feature of this period is the abrupt decline in 17β-estradiol (E2) levels, a hormone with cardioprotective effects. Ovarian hormones are associated with biochemical and functional changes, including impairment of the electron transport chain (CTE) and reduced ATP production, which contribute to mitochondrial dysfunction and increase the risk of developing cardiovascular diseases (DCVs). Resistance training has emerged as an effective non-pharmacological intervention for attenuating the deleterious effects of menopause, promoting improvements in mitochondrial function, hemodynamic parameters, and cardiovascular plasticity. Objective:This study investigated the impacts of ovariectomy, as an experimental model, on mitochondrial bioenergetics in left ventricular cardiomyocytes of Wistar rats, as well as the efficacy of Resistance Training (RT) as a therapeutic strategy to mitigate the effects caused by the reduction of ovarian hormones. Methodology: Twenty Wistar rats were used, divided into four experimental groups (five animals per group): INT-SED (intact sedentary), INT-RT (intact trained), OVX-SED (ovariectomized sedentary), and OVX-RT (ovariectomized trained). The analyses included: gene expression by RT-qPCR of mitochondrial complexes (C1, C2, C3, C4, and ATP synthase) and citrate synthase (CS); high-resolution mitochondrial respiration (Oroboros®); and maximum loading capacity. Results: Ovariectomy significantly impaired mitochondrial function in the left ventricular cardiomyocytes, as well as markedly reduced oxygen consumption in coupled respiratory states (S3 and S3Suc), in addition to decreasing the expression of CTE complexes. Conversely, resistance training (RT) was able to promote both functional and molecular improvements, with a significant increase in O₂ consumption and recovery of mitochondrial complex expression.
Effects of ovariectomy and resistance training on mitochondrial energy function and metabolim of left ventricular cardiomyocytes
Keywords: Ovariectomia; Bioernergética Mitocondrail; Cardiomiócitos; Ventrículo Esquerdo; Menopausa; Treinamento Resistido; Ovariectomy; Bioenergetics Mitochondrial; Cardiomyocytes; Ventricle Left; Menopause; Resistance Training; CIENCIAS BIOLOGICAS::FISIOLOGIA; 3. Saúde e Bem-Estar